EFEKTIVITAS VIRTUAL REALITY (VR) SEBAGAI DISTRAKSI DALAM PENATALAKSANAAN DENTAL PADA ANAK USIA 4-12 TAHUN : SCOPING REVIEW - Darmawangsa, Darmawangsa; Yandi, Satria; Adha, Agung Anugerah (Universitas Baiturrahmah, 2024)
Introduction: Dental anxiety in children aged 4-12 years is an obstacle in dental and oral health care. Anxiety management such as distraction is needed, namely a method to shift the child's focus to other things, such as the use of Virtual Reality (VR). Virtual Reality (VR) is an audiovisual distraction media that can reduce the level of anxiety and pain and unpleasant situations by displaying three-dimensional images along with VR glasses and their voices on the headset. Aim: The purpose of this study was to examine the advantages and disadvantages of Virtual Reality (VR) as a distraction in dental management in children aged 4-12 years, cases of dental management using VR and, the effectiveness of Virtual Reality (VR) as a distraction in dental management in children aged 4-12. Method: The literatures in this review was obtained through searches of the PubMed, Science Direct, and Google Scholar databases using specific keywords along with inclusion and exclusion criteria. Result: The findings of the review of the five articles indicated that virtual reality (VR) was an effective distraction for reducing anxiety and pain levels in children aged 4-12 years undergoing dental treatment. The results of other reviews did not provide specific age range for its use, the ideal duration for its use, the management of adverse effects following its use, or solutions for children who are unable to use it. Conclusion: Virtual reality represents a promising approach for the management of dental management in children aged 4-12 years.